ANALISIS STRATEGI PEMASARAN SECARA ONLINE UNTUK MENARIK MINAT BELI KONSUMEN - Palupi, Rosela; Fasa, Muhammad Iqbal (STAI Darul Qalam Tangerang, 2024)
Online shopping is increasingly in demand by various groups because of the various conveniences provided both in transactions and security. Each e-commerce merchant gives each other bonuses or discounts to attract customer interest. To build teamwork and share various experiences related to sales, it is not uncommon for many online traders to form a community. In fact, another advantage that online traders get is that they can carry out personalized marketing strategies. This personalization strategy is considered quite effective in finding consumers based on the messages sent by traders to consumers. However, basically everything that is done is done to increase sales results. The amount of sales results can be seen from the marketing performance carried out. Through this performance, it can be seen to what extent the trader's performance is in marketing goods. In this case, a trader is someone who plays an active role in sales. With a personalized marketing system, traders can estimate the goods needed by consumers. This research uses qualitative methods, in this type of research the findings are not obtained through statistical procedures or other calculations. The results of this research lead to the statement that online marketing communications and its new forms provide broader coverage, thereby promoting better advertising coverage. Through online marketing, brand development can be better than traditional marketing models. A well-designed website with high-quality information can meet customer needs and create more opportunities to provide significant value to its customers.